ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN DAN LOYALITAS PELANGGAN (Studi Pelanggan Telkom Speedy Kantor Daerah Layanan Telekomunikasi Semarang) - Yohan Wismantoro (MEDIA, 2013)
Customer loyalty is still believed to be a strategy used to determine the success of a company. Model of product quality, service quality is customer-oriented serviceÂ have an impact directly on customer satisfaction and Loyality. Model then tested empirically towards a sample of consumers Speedy Semarang Regional Office of Telecommunications Services by using SEM. The results obtained, the quality of product and service quality and significant positive effect on satisfaction. Similarly, satisfaction have a significant positive effect on loyalty.